2011
DOI: 10.1016/j.forsciint.2010.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Fatal poisoning in drug addicts in the Nordic countries in 2007

Abstract: The frequency of medico-legally examined fatal poisonings in 2007 among drug addicts was investigated in five Nordic countries; Denmark, Finland, Iceland, Norway, and Sweden. The number of deaths, age, sex, place of death, main intoxicant, and other drugs present in blood samples were recorded to obtain national and comparable Nordic data, as well as data to compare with earlier studies in 2002, 1997, and 1991. Norway had the highest incidence of drug addict deaths by poisoning followed by Denmark, with 8.24 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
37
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 5 publications
9
37
0
3
Order By: Relevance
“…Most deaths from poisoning occur outside hospitals and are caused by narcotic substances, most often heroin and various combination poisonings (1,14,15). These types of poisonings are most often dealt with by ambulance personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Most deaths from poisoning occur outside hospitals and are caused by narcotic substances, most often heroin and various combination poisonings (1,14,15). These types of poisonings are most often dealt with by ambulance personnel.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with findings from other studies. [24][25][26]31] It is likely that these drugs are over-represented in samples from decedents, as opiates and cocaine are addictive and carry a greater risk of fatal outcome owing to the risk of central nervous system depression or cardiovascular afflictions, among other complications due to chronic use. [32] Globally, differences exist in patterns of illicit drug use: in Australia, opioids are believed to be responsible for most drug-related deaths, while cocaine has been reported as most commonly detected in drug-related deaths in Florida, USA.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study has shown an increase in fatal drug poisonings among drug addicts in Norway from 1991 to 2007 (2). Drug findings were reported for all forensically examined overdoses in 1991, 1997, 2002 and 2007.…”
Section: Introductionmentioning
confidence: 90%
“…Drug findings were reported for all forensically examined overdoses in 1991, 1997, 2002 and 2007. The overdose mortality in that study was attributed to consumption of illicit drugs, medicinal drugs including opioids and benzodiazepines, as well as of ethanol (2,3). Misuse of illicit drugs had the highest effect on drug related mortality in young and middleaged individuals.…”
Section: Introductionmentioning
confidence: 94%